False-positives in psychopathy assessment : proposing theory-driven exclusion criteria in research sampling - Rosenberg Larsen, Rasmus (Array, 2018)
Recent debates in psychopathy studies have articulated concerns about false-positives in assessment and research sampling. These are pressing concerns for research progress, since scientific quality depends on sample quality, that is, if we wish to study psychopathy we must be certain that the individuals we study are, in fact, psychopaths. Thus, if conventional assessment tools yield substantial false-positives, this would explain why central research is laden with discrepancies and nonreplicable findings. This paper draws on moral psychology in order to develop tentative theory-driven exclusion criteria applicable in research sampling. Implementing standardized procedures to discriminate between research participants has the potential to yield more homogenous and discrete samples, a vital prerequisite for research progress in etiology, epidemiology, and treatment strategies.